2008
DOI: 10.1002/tox.20378
|View full text |Cite
|
Sign up to set email alerts
|

Combined effect of ultraviolet‐B radiation and cadmium contamination on nutrient uptake and photosynthetic pigments in Brassica campestris L. seedlings

Abstract: Environmental and industrial pollution along with increase in ground level UV-B radiation, because of stratospheric ozone depletion, present multiple stresses, which may affect crop photosynthesis and productivity. The present study was undertaken to see interactive effects of heavy metal contamination (Cd(2+)) and UV-B exposure on essential nutrient (Ca(2+), Mg(2+), K(+)) uptake, biomass, and chlorophyll content in mustard (Brassica campestris L.) seedlings. Plants grown in 0.5, 1.0, 2.5, and 5.0 mg L(-1) Cd(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…It inhibits the synthesis of chlorophylls (Chl) (Padmaja et al 1990, Burzyński and Kłobus 2004, Azevedo et al 2005, Shukla et al 2008 and their stable binding to proteins (Horváth et al 1996), thereby decreasing the accumulation of pigment-lipoprotein complexes, particularly photosystem (PS) I (Krupa et al 1987, Sárvári 2005. Ahmed and Tajmir-Riahi (1993) reported that Cd interacted with the protein subunits of light harvesting complex II.…”
Section: Introductionmentioning
confidence: 98%
“…It inhibits the synthesis of chlorophylls (Chl) (Padmaja et al 1990, Burzyński and Kłobus 2004, Azevedo et al 2005, Shukla et al 2008 and their stable binding to proteins (Horváth et al 1996), thereby decreasing the accumulation of pigment-lipoprotein complexes, particularly photosystem (PS) I (Krupa et al 1987, Sárvári 2005. Ahmed and Tajmir-Riahi (1993) reported that Cd interacted with the protein subunits of light harvesting complex II.…”
Section: Introductionmentioning
confidence: 98%
“…Nevertheless, nothing is known about the influence of UV radiation on Hg accumulation and toxicity in aquatic plants, and very few studies have been conducted on the interactive effects of UV and metals in general. UV radiation has been shown to promote metal accumulation, notably for Ni and Cd in Cucumis sativus, Pisum sativum, seedlings of Glycine max, and seedlings of Brassica campestris (Agrawal & Mishra, 2009, Mishra et al, 2010, Prasad, 2005, Shukla et al, 2008. Furthermore, the accumulation of Cu by E. nuttallii was strongly promoted by UV, resulting in more than twice higher ratio between Cu concentrations in shoots and those in the medium under combined UV + Cu exposure as compared to Cu alone (Regier et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the accumulation of Cu by E. nuttallii was strongly promoted by UV, resulting in more than twice higher ratio between Cu concentrations in shoots and those in the medium under combined UV + Cu exposure as compared to Cu alone (Regier et al, 2015). Moreover, UV and metals seemed to have additive effects on physiological processes, such as photosynthetic efficiency, oxidative stress and nutrition (Agrawal & Mishra, 2009, Mishra et al, 2010, Prasad, 2005, Regier et al, 2015, Shukla et al, 2008. To our knowledge, no studies dealing with the combined exposure of aquatic plants to Hg and UV exist.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1 illustrates the effects of Cd as a potent inhibitor of photosynthesis. Photosynthesis inhibition may be attributed to diminished chlorophyll biosynthesis (Shukla et al 2008), interrupted O 2 - evolving reactions of PSII and altered electron flow around PSI and PSII (Mallick and Mohn 2003). Cd hampers Calvin cycle by slowing down activity of various enzymes hence resulting in decreased photosynthesis (Ying et al 2010).…”
Section: Introductionmentioning
confidence: 99%